Search for fourth sound propagation in supersolid 4He: Твердый гелий - Aoki, Y.; Lin, X.; Kojima, H. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2008)
A systematic study was carried out to search for fourth sound propagation solid 4He samples below 500 mK down to 40 mK between 25 and 56 bar using the techniques of heat pulse generator and titanium superconducting transition edge bolometer. If solid 4He is endowed with superfluidity below 200 mK as indicated by recent torsional oscillator experiments, theories predict fourth sound propagation in such supersolid state. If found, fourth sound provides a convincing evidence for superfluidity and a new tool for studying the new phase. To search for a fourth sound-like mode, the response of the bolometers to heat pulses traveling through cylindrical samples of solids grown with different crystal qualities. Bolometers with increasing sensitivity were constructed. The heater generator amplitude was reduced to the sensitivity limit to search for any critical velocity effects. The fourth sound velocity is expected to vary as µ Ör̅s̅/̅r̅. Searcheswere made for signature in the bolometer response with such characteristic temperature dependence. The measured response signal has not so far revealed any signature of new propagating mode within the temperature excursion of 5 mK from the background signal shape. Possible reasons for this negative result are discussed. Prior to the fourth sound search, the temperature dependence of heat pulse propagation was studied as it transformed from «second sound» in the normal solid 4He to the transverse ballistic phonon propagation. Our work extended the studies by Narayanamurti and Dynes [Phys. Rev. B12, 1731 (1975)] to higher pressures and to lower temperatures. The measured transverse ballistic phonon propagation velocity remained constant, within 0.3% scatter of data below 100 mK at all pressures and revealed no indication for an onset of supersolidity. The overall dynamic thermal response of solid to heat input was found to depend strongly on the sample preparation procedure.